A Review of property manager's competency in managing green building / Syamim Jaafar and Nor Aini Hj. Salleh - Syamim, Jaafar; Nor Aini, Hj. Salleh (Universiti Teknologi MARA, Perak, 2017)
The insufficient property manager competency in handling operation and maintenance work often overshadows the benefits from green building development. The uniqueness of green building design makesit different with traditional building and need expertise to handle it. Thus, this study intends to determine the competencies required by property manager in managing green buildings. The reviews from previous research were conducted and study indicatesfour main competency elements, which are knowledge,skill, ability and other characteristics for property managers to manage green buildings. This research gives a significant impact for property managers in providing an effective and efficient green building management